2022
DOI: 10.1186/s40249-022-00969-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the genetic diversity of Giardia intestinalis in isolates from outbreaks in New Zealand

Abstract: Background Giardia intestinalis is one of the most common causes of diarrhoea worldwide. Molecular techniques have greatly improved our understanding of the taxonomy and epidemiology of this parasite. Co-infection with mixed (sub-) assemblages has been reported, however, Sanger sequencing is sometimes unable to identify shared subtypes between samples involved in the same epidemiologically linked event, due to samples showing multiple dominant subtypes within the same outbreak. Here, we aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…However, the outbreak in Wellington 2013 showed peaks at N−2 (unexpected result because they should be a multiple of 3) and N−3 and the outbreak in Taranaki 2021 presented multiple peaks. None reached the level of support suggested by Dettwiler et al (2021); however, further analyses such as metabarcoding might identify mixed infections, including mixed family subtypes and species (Garcia-R et al, 2021;Ogbuigwe et al, 2022).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the outbreak in Wellington 2013 showed peaks at N−2 (unexpected result because they should be a multiple of 3) and N−3 and the outbreak in Taranaki 2021 presented multiple peaks. None reached the level of support suggested by Dettwiler et al (2021); however, further analyses such as metabarcoding might identify mixed infections, including mixed family subtypes and species (Garcia-R et al, 2021;Ogbuigwe et al, 2022).…”
Section: Discussionmentioning
confidence: 81%
“…None reached the level of support suggested by Dettwiler et al . ( 2021 ); however, further analyses such as metabarcoding might identify mixed infections, including mixed family subtypes and species (Garcia-R et al ., 2021 ; Ogbuigwe et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining assemblages have narrow host ranges, namely, C and D are associated with dogs and other canids, E with livestock, F with cats, G with rodents, and H with seals. Metabarcoding at the glutamate dehydrogenase gdh locus showed that assemblage B comprises multiple variants [176]. Currently, the possibility that Giardia assemblages could represent distinct species is under consideration [15].…”
Section: Giardia Intestinalismentioning
confidence: 99%
“…The pathogenic mechanism of Giardia spp. includes disruption of the mucus layer and the gastrointestinal epithelium [176,179].…”
Section: Giardia Intestinalismentioning
confidence: 99%
“…The clinical picture of giardiasis is greatly influenced by the host’s immune response, duration of infection, virulence, and infectious dose of the parasite. The main symptoms that may appear during infection are nausea, diarrhea (followed by dehydration), abdominal pain, vomiting, and flatulence [ 3 , 4 ]. During the life cycle, the protozoan forms a mobile trophozoite and an invasive cyst [ 5 ].…”
Section: Introductionmentioning
confidence: 99%